Assumptions and perceptions of food wasting behavior and intention to reduce food waste in the case of Generation Y and Generation X - László Mucha; Titanilla Oravecz (Scientific Reports)
Abstract One of the global problems of our time is food waste that is most significant at the household level. There is a lack of research that focus on the food-wasting behavior of the main breadwinner groups in society, generations Y and X. To fill this gap, the purpose of this study is to analyse the factors that influence the food-wasting behavior of these groups. From data of a representative sample of 1,665 respondents by using structural equation modeling it is shown that the intention of reducing food waste is positively influenced by attitudes, health-, price and environmental consciousness, planning routines and ecological motives. The results show that influences from the immediate environment and the media are not effective, therefore programs dealing with the future of the Earth, children and sustainability, which strengthen environmental and ecological awareness and planning routines in generations X and Y are recommended.